Ethnic differences in preterm birth in Southwest China, 2014-2018: A population-based observational study - Cao, Guiying; Yuan, Yanling; Kong, Cai; Liu, Jue; Liu, Min; Ye, Hanfeng (Frontiers in Medicine, 2022)
Objective This study used data from Yunnan, a multiethnic province, to explore the differences in preterm birth across ethnicities. Methods A population-based observational study was conducted based on data from the National Free Preconception Health Examination Project in rural Yunnan from Jan 1, 2014 to Dec 31, 2018. Pregnancies with at least one livebirth were included in this study. We estimated the rates and 95% confidence intervals (CIs) of overall preterm birth (born <37 weeks’ gestation), moderate to late preterm birth (born between 32 and <37 weeks’ gestation), very preterm birth (born between 28 and 31 weeks’ gestation), and extremely preterm birth (born <28 weeks’ gestation) across maternal ethnicity and compared them using log-binomial regressions. Multivariate log-binomial regressions were used to assess the association between maternal ethnicity and preterm birth with adjustment for potential confounders. Results Among 195 325 women who delivered at least one live baby, 7.90% (95% CI, 7.78%-8.02%) were born preterm. The rates of moderate to late preterm birth, very preterm birth, and extremely preterm birth were 6.20% (95% CI, 6.09%-6.30%), 1.18% (95% CI, 1.13%-1.23%), and 0.52% (95% CI, 0.49%-0.56%), respectively. The rates of overall preterm birth, moderate to late preterm birth, very preterm birth, and extremely preterm birth differed across maternal ethnicity. The preterm birth rates in Dai (10.73%), Miao (13.23%), Lisu (12.64%), Zhuang (11.77%), Wa (10.52%), and Lagu (12.34%) women were significantly higher than that in Han women, and the adjusted relative risks were 1.45 (95% confidence interval [CI], 1.36, 1.54), 1.74 (95% CI, 1.62, 1.86), 1.60 (95% CI, 1.47, 1.75), 1.60 (95% CI, 1.46, 1.75), and 1.40 (95% CI, 1.22, 1.60), respectively. There was no difference in preterm birth rate between Han women and Hani, Bai, or Hui women. Conclusion This study found notable differences in the rates of preterm birth and its sub-categories across maternal ethnicities, which were especially higher in ethnic minority women. The findings suggest that greater efforts to reduce ethnic inequalities in preterm birth. Future studies are warranted to understand the drivers of ethnic inequalities in preterm birth in China.